Demonstration of high-reconfigurability and low-power strong physical unclonable function empowered by FeFET cycle-to-cycle variation and charge-domain computing - Taixin Li; Xinrui Guo; Franz Müller; Sukhrob Abdulazhanov; Xiaoyang Ma; Hongtao Zhong; Yongpan Liu; Vijaykrishnan Narayanan; Huazhong Yang; Kai Ni; Thomas Kämpfe; Xueqing Li (Nature Communications)
Abstract Physical unclonable functions (PUFs) are of immense potential in authentication scenarios for Internet of Things (IoT) devices. For creditable and lightweight PUF applications, key attributes, including low power, high reconfigurability and large challenge-response pair (CRP) space, are desirable. Here, we report a ferroelectric field-effect transistor (FeFET)-based strong PUF with high reconfigurability and low power, which leverages the FeFET cycle-to-cycle variation throughout the workflow and introduces charge-domain in-memory computing. The proposed PUF cells are fabricated at 28 nm node, and the experimental measurements reveal high uniformity, uniqueness and repeatability. Remarkably, our PUF achieves near-ideal reconfigurability and ultra-low 1.89fJ per bit readout energy, significantly outperforming the state-of-the-art PUFs. Furthermore, we show that the PUF is robust against parameter variations and resilient to machine learning (ML) attacks. These performances highlight the great promise of the FeFET-based strong PUF as a feasible IoT security solution.